2022
DOI: 10.1097/acm.0000000000004987
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Instrument to Measure the Community Well-Being of Residency Programs

Abstract: PurposeTo develop and validate the Residency Community Well-Being (RCWB) instrument, a novel instrument to measure the subjective community well-being of an individual residency program, and to explore differences in RCWB scores between demographic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Vermette and colleagues found that residents working more than 60 hours per week had lower scores on the overall RCWB scale and its subscales. 5 This association is consistent with the hypotheses that effective physician well-being efforts must include reducing work hours by improving workplace efficiency. 7 One study estimated that the majority of internal medicine residents spent more than 4 hours on documentation per day, with far fewer reporting spending equivalent time engaged in direct patient care.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…Vermette and colleagues found that residents working more than 60 hours per week had lower scores on the overall RCWB scale and its subscales. 5 This association is consistent with the hypotheses that effective physician well-being efforts must include reducing work hours by improving workplace efficiency. 7 One study estimated that the majority of internal medicine residents spent more than 4 hours on documentation per day, with far fewer reporting spending equivalent time engaged in direct patient care.…”
supporting
confidence: 84%
“…3,4 In this issue, Vermette and colleagues' report emphasizes the importance of shifting focus from individual trainees to training programs and provides a means to measure residency climate factors associated with burnout. 5 The authors' novel Residency Community Well-Being (RCWB) instrument attempts to assess the community well-being domain, which overlaps with related domains described elsewhere as workplace climate 6 and culture of wellness. 7 Efforts to create a culture of wellness may be the most unexplored frontier in the field of physician wellness.…”
mentioning
confidence: 99%
See 3 more Smart Citations